Severe Maternal Morbidity: post-traumatic suffering and social support - Mônica Silva Silveira; Ricardo Queiroz Gurgel; Íkaro Daniel de Carvalho Barreto; Larissa Paes Leme Galvão; Marlizete Maldonado Vargas
ABSTRACT Objective: To assess the relationship of post-traumatic stress symptoms and the perception of social support in women submitted to Severe Maternal Morbidity (SMM). Method: A prospective cohort study, with 549 women from public hospitals. The Impact of Events and Social Support scales were used. Results: Women with SMM were from the State countryside (p=0.046), with low schooling (p=0.039) and did not work (p<0.001). They presented higher consumption of alcoholic beverages (p<0.001), did not perform prenatal (p<0.001), and were older (28.15 ± 28 years). Women with SMM had higher mean values of avoidance behavior (24.32, SD: 4.16), intrusive thinking (18.28, SD: 3.80), lower social support (0.11, SD: 0.001) with large effect size and lower social support satisfaction (0.69; SD: 0.19), with small effect size. Conclusion: SMM is a differential and negative factor for women's mental health, and social support can favor their coping.